Evaluation of different formulations of gellan gum-based hydrogels for tissue engineering of intervertebral disc - Lee, S. K. (2012)
Gellan gum based-hydrogels present advantageous features for application as acellular and cellular nucleus pulposus (NP) substitutes due to the possibility of fine-tuning its physico-chemical and biological properties. In this study, ionic-crosslinked hydrogel discs were produced by means of mixing a raw and chemically modified material, i.e., high acyl gellan gum (HAGG) and methacrylated low acyl gellan gum (GG-MA), respectively. The hydrogel discs were characterized in terms of its mechanical properties and degradation/swelling ability. The biocompatibility of the different hydrogel formulations was assessed in vitro using NP rabbit cells isolated from the intervertebral disc. The biological performance of the developed gellan gum-based hydrogels formulations was evaluated by: (i) culturing of NP cells in the presence of the hydrogel leachables, and (ii) seeding or encapsulation of the NP cells within the hydrogels. The present work demonstrated that as HAGG content increases, the modulus of the hydrogels decreases. Moreover, the increase of the HAGG content induces a higher weight loss of the GG-MA/HA-GG formulation as compared to GG-MA hydrogel. The in vitro study revealed that hydrogels are non-cytotoxic and support the encapsulation of rabbit NP cells. The methacrylated gellan gum and formulations possessing high acyl gellan gum present tunable properties that may be interesting for application as NP substitutes.